Understanding the Pathophysiological Actions of Tau Oligomers: A Critical Review of Current Electrophysiological Approaches - Hill, Emily; Wall, Mark J.; Moffat, Kevin G.; Karikari, Thomas K. (Frontiers in Molecular Neuroscience, 2020)
Tau is a predominantly neuronal protein that is normally bound to microtubules, where it acts to modulate neuronal and axonal stability. In humans, pathological forms of tau are implicated in a range of diseases that are collectively known as tauopathies. Kinases and phosphatases are responsible for maintaining the correct balance of tau phosphorylation to enable axons to be both stable and labile enough to function properly. In the early stages of tauopathies, this balance is interrupted, leading to dissociation of tau from microtubules. This leaves microtubules prone to damage and phosphorylated tau prone to aggregation. Initially, phosphorylated tau forms oligomers, then fibrils and ultimately neurofibrillary tangles (NFTs). It is widely accepted that the initial soluble oligomeric forms of tau are probably the most pathologically relevant species. However, there is relatively little quantitative information to explain exactly what their toxic effects are at the individual neuron level. Electrophysiology provides a valuable tool to help uncover the mechanisms of action of tau oligomers on synaptic transmission within single neurons. Understanding the concentration-, time-, and neuronal compartment-dependent actions of soluble tau oligomers on neuronal and synaptic properties is essential to understanding how best to counteract their effects and to develop effective treatment strategies. Here, we briefly discuss the standard approaches used to elucidate these actions, focusing on the advantages and shortcomings of the experimental procedures. Subsequently, we describe a new approach that addresses specific challenges with the current methods, thus allowing real-time toxicity evaluation at the single-neuron level.